Weed control efficiency of unmanned aerial vehicle spray in replanting oil palm plantation areas - Che Ruzlan, Kamalul Adham; Bakar, Shahrul Azman; Che Manan, Che Ahmad Hafiz; Mohd Noor, Muhammad Khairul Anuar; Abd Latif, Mohd Razman; Zainal Abidin, Cik Mohd Rizuan; Jusoh, Mashitah; Ahmad Hamdani, Muhammad Saiful (Cambridge University Press, 2024)
Efficient chemical weed management considers precise application of herbicides, maximizing herbicide retention and absorption, reducing the impact of abiotic factors, and mitigating off-target movement in order to optimize herbicide efficacy. Hence, this study assessed the employability and cost-efficiency of an unmanned aerial vehicle (UAV) for preplanting application and postemergence selective weed control of grasses infesting legume cover crops (LCCs) in an immature oil palm (Elaeis guineensis Jacq.) plantation. Field experiments were conducted in 2020 and 2021 at a research center and an oil palm replanting area in Jerantut, Pahang, Malaysia. Droplet deposition and distribution analyses revealed that the pressure at 0.25 MPa yielded better spray coverage and increased droplet counts compared with 0.15 MPa. For preplanting application, both the UAV and mist blower resulted in total weed control. Meanwhile for selective grass control in the LCCs, conventional knapsack sprayer (CKS) application provided slightly better weed control than the UAV over the 12-wk observation. However, a cost-efficiency analysis revealed that UAV spraying yielded economically favorable results for areas greater than 3,000 ha, with potential savings ranging from 4% to 28%. Furthermore, UAV spraying demonstrated superior operational efficiency and reduced working hours by 37%, water consumption by 91%, and human labor expenses by 81% compared with both conventional methods. These findings underscore the potential of UAV-based spraying for large-scale weed control in oil palm plantations and highlight its efficiency, comparable effectiveness, and cost-saving benefits.